The safety, efficacy and cost-effectiveness of the Maxm Skate, a lower limb rehabilitation device for use following total knee arthroplasty: study protocol for a randomised controlled trial - Matthew G. Liptak; Annika Theodoulou; Billingsley Kaambwa; Steve Saunders; Scott W. Hinrichs; Richard J. Woodman; Jeganath Krishnan (Trials, 2019)
Abstract Background Physical rehabilitation is required to enhance functional outcomes and overall recovery following total knee arthroplasty (TKA). However, there are no universally accepted clinical guidelines available to consistently structure rehabilitation for TKA patients. A common method is rehabilitation provided in an outpatient setting, on a one-to-one treatment basis. This method is resource-intensive and outcomes must be compared to less costly alternatives such as home-based rehabilitation. The current study will analyse a novel home-based rehabilitation program. The Maxm skate is a portable, lower-limb, postoperative, rehabilitation exercise device for individual use in a hospital or home-based setting. This study was developed to compare the safety, efficacy and cost-effectiveness of the Maxm Skate rehabilitation program to standard rehabilitative care following TKA. The primary outcome is the range of motion (ROM) achieved by patients who received the Maxm Skate program compared to standard care at three months post TKA. Secondary outcomes include patient-reported outcomes, costs and functional evaluations which will be collected at multiple time-points up to 12 months after TKA. Methods This is a single-blinded, randomised controlled trial (RCT) in which 116 eligible participants consented for primary TKA will be randomly allocated to receive either the Maxm Skate rehabilitation program or standard rehabilitative care. Fifty-eight participants per group will provide 90% power (α = 0.05) to detect 10° of difference in ROM between groups at three months after TKA, assuming a within-group standard deviation of 16° and allowing for 5% loss to follow-up. Participants randomised to the Maxm Skate group will use the skate device and accompanying iOS App and sensors to complete rehabilitation exercises, as outlined in the Maxm Skate Rehabilitation Guide. Outcomes will be compared to those receiving standard rehabilitative care. A blinded physiotherapist will evaluate functional outcomes preoperatively and at 2, 4, 6, 12, 26 and 52 weeks after TKA. The functional assessment will include measures of knee ROM, pain, isometric knee strength, balance and knee/thigh circumference. Limited measures will also be assessed at day 2 postoperatively by an alternate, unblinded physiotherapist. Clinical outcome measures will be administered preoperatively and at 6, 12 and 52 weeks postoperatively. An economic evaluation will be conducted and participants will be screened for adverse event occurrences from the time of consent to 12 months postoperatively. Discussion This RCT will be the first to investigate the safety, efficacy and cost-effectiveness of the home-based Maxm Skate Rehabilitation program, in comparison to standard rehabilitative care following primary TKA. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12616001081404p. Registered on 11 August 2016.